Implementasi Kebijakan Lanal Kotabaru (Di Kalimantan Selatan) Dalam Pemberdayaan Masyarakat Nelayan (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2017)
In developing countries, fishermen are a group of society experiencing social problems such aspoverty and education. The marine high posttension of Indonesia should heve made thefishermen wealthy. In contrast, their economic condition is still so far from wealth, so theyreally need empowerment in order to reach their better future. Kotabaru Lanal Station is one ofthe institutions conducting empowerment for the fishermen in the its responsibility area throughthe empowering programs. To conduct the empowering programs, Kotabaru Lanal Stationcooperates with Kotabaru Regency Government, the empowerment partner.This qualitative research uses the main theory of George Edward III Implementation consistingof four variables, i.e. communication, bureaucracy structure, resources, and disposition. Thepolicy implementation of Kotabaru Lanal Station in fishermen community empowerment hasbeen done well through socialization activities, social assistances, and training, that impactingpositively to Kotabaru fishermen development. The blocking factors to conduct the programsare the minimal budget and the limited human resources of Kotabaru Naval Station. Thesupporting factors to conduct the programs are the supports of Kotabaru Naval Stationpersonnels, Kotabaru Regency Government, and the fishermen.